Prognostic value of bone marrow involvement by clonal immunoglobulin gene rearrangements in follicular lymphoma. Issue 12 (18th September 2014) - Berget, Ellen; Helgeland, Lars; Liseth, Knut; Løkeland, Turid; Molven, Anders; Vintermyr, Olav Karsten
Abstract : Aims: We aimed to evaluate the prognostic value of routine use of PCR amplification of immunoglobulin gene rearrangements in bone marrow (BM) staging in patients with follicular lymphoma (FL). Methods: Clonal rearrangements were assessed by immunoglobulin heavy and light-chain gene rearrangement analysis in BM aspirates from 96 patients diagnosed with FL and related to morphological detection of BM involvement in biopsies. In 71 patients, results were also compared with concurrent flow cytometry analysis. Results: BM involvement was detected by PCR in 34.4% (33/96) of patients. The presence of clonal rearrangements by PCR was associated with advanced clinical stage (I–III vs IV; p<0.001), high FL International Prognostic Index (FLIPI) score (0–1, 2 vs ≥3; p=0.003), and detection of BM involvement by morphology and flow cytometry analysis (p<0.001 for both). PCR-positive patients had a significantly poorer survival than PCR-negative patients (p=0.001, log-rank test). Thirteen patients positive by PCR but without morphologically detectable BM involvement, had significantly poorer survival than patients with negative morphology and negative PCR result (p=0.002). The poor survival associated with BM involvement by PCR was independent of the FLIPI score (p=0.007, Cox regression). BM involvement by morphology or flow cytometry did not show a significant impact on survival. Conclusions: Our results showed that routine use of PCR-based clonality analysis significantly improved the prognostic impact of BM staging in patients with FL. BM involvement by PCR was also an independent adverse prognostic factor.